"El tiempo de... ": división del tiempo y ciclo de reproducción entre los yagua del oriente peruano - Frayse-Chaumeil, Josette (1985)
This is a presentation and description of the main activities according to the annual Yagua cycle. This article also deals with the calendar and the division of time in their society.